(untitled) (Economics and region, 2025)
This study introduces and evaluates the Infrastructure Risk Management Method (IRMM), with particular emphasis on the Infrastructure Risk Index (IRI) as a quantitative measure to identify and mitigate risks in infrastructure projects. A two-year case study was conducted at Mastergaz, a leading infrastructure firm, involving fifty projects. Data were collected through structured interviews and surveys administered to project managers and field technicians. The IRI was calculated by integrating criticality, vulnerability, and external influences, and then analyzed in conjunction with historical performance metrics. The findings demonstrate a strong correlation between IRI values and observed failure rates, highlighting the IRMM’s predictive capability. Dynamic assessments allowed continuous monitoring and informed preventive strategies, such as maintenance schedules and contingency plans, thereby reducing infrastructure failures. Scalability was also evident, suggesting broader applicability in sectors like transportation and energy. By integrating real-time data and aligning with existing project management frameworks, the IRMM advances infrastructure risk management practices. This dynamic, proactive approach fosters improved decision-making and resilience in evolving operational environments, offering a valuable foundation for further research and practical implementation.